The Impact of Afghanistan's Changed Situation on India's Geo-environment (Asian Journal of Social Science Studies, 2022)
Afghanistan's changed situation was one of the biggest international changes in 2021, causing violent shocks to the world. As an important neighboring country of Afghanistan, India has significant economic and security interests in Afghanistan. The change in Afghanistan has not only directly affected the bilateral relations between India and Afghanistan, but also has triggered a new round of regional power games involving India, Pakistan, Russia, Iraq and other countries. At the same time, the change in Afghanistan is also related to the adjustment of United States’ global strategy. As a result, the situation in Afghanistan has had a profound and extensive impact on India's geo-environment.